Pola Asuh Orang Tua pada Perilaku Anak dalam Pendidikan Agama Islam - Ratna Fatmawati; Masykur H Mansyur; Neng Ulya (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Parenting is a way for parents to educate and teach everything related to children's lives, by teaching commendable behavior in accordance with Islamic religious education, so that children's life patterns become regular and directed and can be useful for many people. This article aims to find out how good parenting for children is in accordance with Islamic religious education, because children's behavior in everyday life will have an impact on their personal and social life, so that children's behavior is in accordance with Islamic religious education, this article aims to add literacy in education. This article uses a descriptive method with a qualitative approach. The results in this article based on the discussion found three parenting patterns in providing education to children, parenting that often occurs in the family environment is authoritarian and permissive parenting, this has a major impact on behavior change in children in a negative direction. Because the authoritarian and permissive parenting is not ideal in the application of the family environment.